PGC-1α modulates necrosis, inflammatory response, and fibrotic tissue formation in injured skeletal muscle. Issue 1 (December 2016) - Dinulovic, Ivana; Furrer, Regula; Di Fulvio, Sabrina; Ferry, Arnaud; Beer, Markus; Handschin, Christoph
Abstract Background Skeletal muscle tissue has an enormous regenerative capacity that is instrumental for a successful defense against muscle injury and wasting. The peroxisome proliferator-activated receptor γ coactivator 1α (PGC-1α) exerts therapeutic effects in several muscle pathologies, but its role in damage-induced muscle regeneration is unclear. Methods Using muscle-specific gain- and loss-of-function models for PGC-1α in combination with the myotoxic agent cardiotoxin (CTX), we explored the role of this transcriptional coactivator in muscle damage and inflammation. Results Interestingly, we observed PGC-1α-dependent effects at the early stages of regeneration, in particular regarding macrophage accumulation and polarization from the pro-inflammatory M1 to the anti-inflammatory M2 type, a faster resolution of necrosis and protection against the development of fibrosis after multiple CTX-induced injuries. Conclusions PGC-1α exerts beneficial effects on muscle inflammation that might contribute to the therapeutic effects of elevated muscle PGC-1α in different models of muscle wasting.